A Healthy Climbing: The Critical Care Approach - Mehrnoush Hedayati (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Critical assessment, as an active and organized process, has become an essential activity for a better understanding of scientific texts and clarifications of goals, highlights, and outcomes, as well as the dynamics of studies over the last few decades. This activity, however, is often accompanied by objection, and sometimes abrupt bias, which greatly reduces its effects. Critical assessment is one of the components or functions of Critical Thinking. Critical Thinking means something more than just looking for the problems; rather, it has tried to consider a subject from different aspects. Unfortunately, one of the common problems of critical assessment is the excessive focus on rational critique processes, and the separation of the logic from emotions. In this paper, the possibility of presenting a cognitive-emotional approach was taken into account to criticize and to answer the question of how much emotional components can be considered in this cognitive and maybe unpleasant activity. The paper has tried to find out What the requirements of paying attention to the value and emotional components during this process are, and how we relate Critical Thinking to Caring Thinking.  In response to these questions, the concept of Critical Care is presented by describing Critical Thinking and Caring Thinking as well as its components.